Effects of a Novel, Non-toxic Histone Deacetylase Inhibitor on Hippocampal Memory Formation, Histone Acetylation, and Bdnf Gene Expression in Male Mice - (:unkn) unknown (My University, 2021)
Memory dysfunction is a common symptom of aging, neuropsychiatric disorders, and neurodegenerative disorders, yet truly effective treatments for memory loss do not exist. De novo gene transcription is a molecular requirement for long-term memory formation. The transcription of genes related to synaptic plasticity and learning are regulated in part by histone acetylation, an epigenetic mechanism that regulates chromatin accessibility. Pharmacological compounds that maintain histone acetylation, called histone deacetylase inhibitors (HDACi), enhance memory by preventing deacetylation of core histone proteins, which initiates binding of transcriptional machinery to open chromatin. Therefore, HDACi are potentially promising therapeutics that could be used to prevent or delay memory loss associated with aging and other disorders. However, existing HDACi have poor solubility and undesirable toxicity. We collaborated with Drs. Mahmun Hossain and Doug Steeber of the University of Wisconsin-Milwaukee to develop a novel brain-penetrant HDACi compound, MJM-1, that shows minimal toxicity and is capable of crossing the blood brain barrier. The goal of this study was to determine the extent to which MJM-1 enhances spatial and object recognition memory consolidation, alters hippocampal histone acetylation, and modifies hippocampal bdnf expression in male mice. Here, we demonstrate that post-training i.p. administration of MJM-1 enhances hippocampus-dependent spatial, but not object recognition, memory consolidation in male mice. Interestingly, however, we observed no treatment effects of MJM-1 on hippocampal histone acetylation when administered alone or immediately following object training. Finally, we also demonstrate that MJM-1 does not alter hippocampal expression of bdnf exons I or IV. Our results suggest that MJM-1 likely enhances spatial memory consolidation by affecting acetylation states of nonhistone proteins. These results underscore the need to better understand the ways in which systemic HDACi administration affects numerous other nonhistone substrates that can also promote beneficial effects on cognition.
Keywords: Epigenetics; Hippocampus; Histone deacetylase inhibitor; Object Recognition Memory; Spatial Memory